1992
DOI: 10.1007/bf02923585
|View full text |Cite
|
Sign up to set email alerts
|

Activity and isoenzyme composition of peroxidase and esterase in fertile and male-sterile lines of tomatoes (Lycopersicon esculentum Mill.)

Abstract: Activity and isoenzyme composition of peroxidase and esterase in fertile and male.sterile lines of tomatoes (Lycopersicon esculentum Mill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…It would be difficult to comment on the causes that might determine higher callus frequency in the abnormal anthers, as numerous, and various events are known to cause the genetic anther defects (Kaul, 1988;Markova et al, 1992Markova et al, , 1994Chaudhury, 1993). For this reason, we do not conclude that stamens and/or pollen abnormalities in principle would enhance callus formation.…”
Section: Resultsmentioning
confidence: 69%
“…It would be difficult to comment on the causes that might determine higher callus frequency in the abnormal anthers, as numerous, and various events are known to cause the genetic anther defects (Kaul, 1988;Markova et al, 1992Markova et al, , 1994Chaudhury, 1993). For this reason, we do not conclude that stamens and/or pollen abnormalities in principle would enhance callus formation.…”
Section: Resultsmentioning
confidence: 69%
“…Numerous studies have reported that Class III peroxidases are integral to plant growth, development, and physiological processes, especially for pollen production and stress responses. For example, in a study on male sterility in tomatoes, higher overall peroxidase activity was observed in MS stamens compared with that in male fertile stamens ( Markova et al., 1992 ). Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that Class III peroxidases are integral to plant growth, development, and physiological processes, especially for pollen production and stress responses. For example, in a study on male sterility in tomatoes, higher overall peroxidase activity was observed in MS stamens compared with that in male fertile stamens (Markova et al, 1992). Chen et al cloned the Ghpod gene, which contained a conserved domain of Class III peroxidase, and found its expression in the reproductive organs of cotton, particularly pollen, suggesting the involvement of peroxidases in the male reproductive process of angiosperms (Chen et al, 2009).…”
Section: A B Figurementioning
confidence: 99%
“…After that the plants were planted in pots outside to study the phase of IV th leaf and bud-formation. Enzyme extracts preparation were previously described (Markova et al 1992). Electrophoretic resolution was carried out by the method of vertical block electrophoresis in 7.5 % polyacrylamide gel (PAAG) and a continu- …”
Section: Methodsmentioning
confidence: 99%